Internet Survey of Risk Factors Associated With Training and Competition in Dogs Competing in Agility Competitions - Pechette Markley, Arielle; Shoben, Abigail B.; Kieves, Nina R. (Frontiers in Veterinary Science, 2022)
Objective To describe risk factors associated with training and competition in relation to frequency and severity of injuries experienced by agility dogs. Procedures An internet-based survey collected data on competition level variables and training level variables. The primary outcome was history of any injury and a secondary outcome considered history of severe injury (injury lasting >3 months). Logistic regression was used to estimate associations and final models were obtained via backward selection to identify the strongest associations within variables. Results There were 4,197 dogs included in this analysis. Injury was reported for 1,737 (41.4%) dogs and severe injury was reported for 629 (15.0%). In the model with competition level factors, jumping 4” (OR: 1.50) or 2-4” (OR: 1.31) over shoulder height compared to jumping 0-2” lower and competing at national events was associated with increased injury risk, while competing 6+ times on rubber matting was associated with lower risk (OR: 0.62). Training level variables associated with injury risk were age starting jump, teeter, and weave training, with the highest risk observed for dogs starting jump training between 3-18 months but starting weave and teeter training after 18 months of age. Conclusion and Clinical Relevance Many variables thought to be associated with injury risk were not significant in the final model. Starting jump training at an earlier age was associated with greater risk of injury relative to starting after 18 months. It is possible that the high impact of jump training before skeletal maturity may increase the risk of injuries or musculoskeletal conditions. The increased risk of injury in dogs jump 2-4, or 4+ inches higher than shoulder height may be due to increased biomechanical forces during takeoff and landing. Faster dogs may be at higher risk of injury; handlers planning competition around big events or competing at the national level are likely to have faster dogs, and may be less likely to compete on rubber matting. These data provide valuable current insight into the possible effects that training and competition variables may have on injury risk in agility dogs.